Analysis of The Effect of Quality Service and Marketing Relation on Customer Loyalty Through Customer Satisfaction at Ratna Dewi Skin Care Clinic Metropolitan Mall Bekasi - Tri Andari Ratna Widyastuti (Majalah Ilmiah Bijak, 2021)
Companies engaged in services should be able to maintain a good reputation in the eyes of its customers. Good quality service and quality will tend to provide more satisfaction and trust to customers who use services at the company. Regardless of quality service, marketing relation, trust and customer satisfaction then do not expect the company can continue to maintain image in the eyes of customers. This research is aimed to analyze the influence of quality service and trust to customer satisfaction and to analyze the influence of customer satisfaction to customer loyalty.This study uses multiple linear regression analysis and simple regression with SPSS program. The population used is customers who have used facial skin care services at Ratna Dwi Skin Care Metropolitan Mall Bekasi. While the sample used as many as 100 people with sample selection techniques using accidental sampling.Â The results show that there are positive and significant influence between quality service, marketing relation to customer loyalty, There are positive and significant influence between trust on customer satisfaction. There areÂ positive and significant influence between satisfaction and marketing relationship to customer loyalty.